2018
DOI: 10.1101/496877
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disentangling the origins of confidence in speeded perceptual judgments through multimodal imaging

Abstract: AbstractThe human capacity to compute the likelihood that a decision is correct - known as metacognition - has proven difficult to study in isolation as it usually co-occurs with decision-making. Here, we isolated post-decisional from decisional contributions to metacognition by combining a novel paradigm with multimodal imaging. Healthy volunteers reported their confidence in the accuracy of decisions they made or decisions they observed. We found better metacognitive performa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 76 publications
2
18
0
Order By: Relevance
“…The past years have seen a growing interest in elucidating the sources of information that contribute to confidence judgments, as a window into potential computational processes that allow the brain to monitor itself. Converging evidence from very different experimental paradigms suggested that confidence is modulated by motor information concurrent with the first-order response (Faivre et al, 2017;Fleming et al, 2015;Patel et al, 2012;Pereira et al, 2018); for a review see (Anzulewicz, Hobot, Siedlecka, & Wierzchoń, 2019). Here, we set out to directly investigate this possibility.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The past years have seen a growing interest in elucidating the sources of information that contribute to confidence judgments, as a window into potential computational processes that allow the brain to monitor itself. Converging evidence from very different experimental paradigms suggested that confidence is modulated by motor information concurrent with the first-order response (Faivre et al, 2017;Fleming et al, 2015;Patel et al, 2012;Pereira et al, 2018); for a review see (Anzulewicz, Hobot, Siedlecka, & Wierzchoń, 2019). Here, we set out to directly investigate this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have addressed the same question by using different experimental manipulations, that can be broadly grouped as following one of three approaches. A first set of studies have asked participants to rate confidence of observed, rather than committed, actions, whilst letting participants observe only first-order RTs (Patel et al, 2012;Vuillaume, Martin, Sackur, & Cleeremans, 2019) or both RTs and stimuli (Pereira et al, 2018) before making the confidence judgement. A second group of studies have instead manipulated the timing of the confidence judgement relative to that of the first-order response (Siedlecka, Paulewicz, & Wierzchoń, 2016;Wokke, Achoui, & Cleeremans, 2019).…”
Section: Differences With the Existing Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Namely, we continuously tracked the position and kinematics of the mouse that participants used to indicate their first-order response during a motion discrimination task (Dotan, Meyniel, & Dehaene, 2018;Dotan, Pinheiro-Chagas, Al Roumi, & Dehaene, 2019) . In addition, we modeled first and second-order responses as derived from a bounded evidence accumulation process starting when participants initiated a mouse movement (Pereira et al, 2018;Pleskac, Busemeyer, & others, 2010;Resulaj, Kiani, Wolpert, & Shadlen, 2009;Van Den Berg et al, 2016) . Together, these two approaches following a pre-registered plan allowed us to finely characterize decision-making and metacognitive monitoring in schizophrenia in relation to clinical traits while avoiding the typical confounds that may have contaminated previous results in the field.…”
Section: Introductionmentioning
confidence: 99%